Two Pandemic Years Greatly Reduced Young People's Life Satisfaction: Evidence from a Comparison with Pre-COVID-19 Panel Data - Martin Neugebauer; Alexander Patzina; Hans Dietrich; Malte Sandner (Institute of Labor Economics (IZA), 2023)
How much did young people suffer from the COVID-19 pandemic? A growing number of studies address this question, but they often lack a comparison group that was unaffected by the pandemic, and the observation window is usually short. Here, we compared the 2-year development of life satisfaction of German high school students during COVID-19 (N = 2,698) with the development in prepandemic cohorts (N = 4,834) with a difference-in-differences design. We found a decline in life satisfaction in winter 2020/2021 (Cohen's d = -0.40) that was approximately three times stronger than that in the general population and persisted until winter 2021/2022. Young people found some restrictions particularly burdensome, especially travel restrictions, bans on cultural events, and the closure of bars/clubs.
Keywords: I31; I18; J24; 330; COVID-19; well-being; causal analysis; pandemic; adolescents; Germany